A community of excellence - bin Mohammad Suhaini, M (2018)
The Islamic Religious Council of Singapore (Muis), is a statutory board, or a semi- official government agency, under the Singapore government. It is in charge of planning and crafting the religious direction of the Muslim community in Singapore. As a statutory board, it has autonomy from the state to make its own decisions. But when religious direction and state policy overlap, does the autonomy still hold? This statement has implications on the state’s relationship with the Muslim community.his paper argues that Muis’ narratives on these two issues can be shown as being influenced by state narratives and discourses. This is done by using a content analysis on Friday prayer sermons in Singapore in 2017 (n=54). These sermons are written by Muis and read verbatim in most mosques across Singapore each Friday afternoon, and are listened to by the congregants in silent attention. Results have shown that after spiritual and moral exhortation, the Friday prayer sermons focus on building a Singaporean Muslim identity and tackling radicalism. These results are typical of sermons written by an official religious body. Further, the frames used by the sermons to discuss the Singaporean Muslim identity and radicalism overlap with the frames utilised by the state. This paper therefore gives some evidence of the state’s influence in developing Muis’ narratives on national identity and radicalism. It also discusses the implications such a move can have on the Singaporean Muslim community and its relationship with the state.